The The Word Formation Process of Suffixes in â€œLeave Beautifulâ€ Song Album by Astrid S. - Khusna, Febriana Aminatul; Fadilah, Dini Nurlaila (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
Linguistics is the science that tries to understand the language from the perspective of its internal structure. The affix is the one of part I the linguistics study. The affix word is one of the vital things in a grammar. An affix serves to form meaning in a word. A suffix is an affix that is placed at the end of the word. This study aims to analyze the existence of the suffix in Astrid S.'s "Laeave Beautiful" album. This album has 16 songs. In analyzing the suffix, the researcher uses Yule's (2020) theory. Qualitative descriptive method and content analysis as the instrument is used in this research to find the valid data. The result, researchers found 74 words that use the suffix. with six types of suffixes; -s / -es, -ed, -fu, -ing, -ly and -ize. The researchers also classified these suffixes into derivational and inflectional groups. The researchers found that there are 51 inflectional types and 23 derivational types.